Physical Activity and cardiovascular function in 9-year-old schoolchildren: implications for health and well-being - Irina Masliak; Margarita Mameshina; Marina Jagiello (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Sedentary lifestyles are major risk factors for cardiovascular diseases later in life. Identifying the potential benefits of physical activity for the cardiovascular health of children is crucial for developing effective strategies to promote healthy habits and prevent future health problems. Purpose of the article is to investigate the relationship between physical activity and cardiovascular function in 9-year-old schoolchildren, taking into account the gender.